Miʻmārān-i Pākistān : jin ke fikrī aur ʻamlī kāvishoṉ se Pākistān maʻraz̤-i vujūd meṉ āyā / az Munshī ʻAbdurraḥmān Ḵẖān. - ʻAbdurraḥmān Ḵẖān, 1913- (Shaiḵẖ Ikaiḍamī, 1976)
Historical study of the Pakistan movement; includes biographical sketches of prominent Muslim leaders of the movement.